ApoA-1 infusion reduces arterial cholesterol and myocardial lesions in a rat model of cardiac dysfunction and insulin resistance - Borthwick, F.; Warnakula, S.; Mangat, R.; Uwiera, R.; Russell, J.; Kelly, S.; Lee, C.; Hryshko, L.; Mamo, John; Rye, K.; Lopaschuk, G.; Proctor, S. (Elsevier Ireland, 2012)
OBJECTIVE Low plasma high-density lipoprotein cholesterol (HDL-C) concentration is associated with the metabolic syndrome (MetS) and increased prevalence of cardiovascular disease (CVD). Animal and human studies report infusion of apolipoprotein A-1 (apoA-1) can reduce endothelial dysfunction, and/or induce regression of atherosclerosis. However, the direct mechanisms underlying the vascular benefits of either apoA-1 or HDL-C remain unclear. In this study, we assessed the ability of reconstituted HDL (rHDL) to improve vascular complications of MetS, including left ventricular (LV)-hypertrophy, arterial cholesterol deposition and myocardial lesion development. METHODS AND RESULTS Obese insulin resistant (IR) JCR:LA-cp rats were infused with rHDL (0.4 mg/kg) over 3 days before assessing cardiac function (Echocardiography) at days 7 and 50 post-infusion, as well as haematoxylin and eosin staining of myocardial lesions at day 50. Acute ex vivo arterial cholesterol deposition was assessed with acute infusion of rHDL ex-vivo. Infusion of rHDL partially corrected abnormal diastolic compliance (18%; *p < 0.05) and improved parameters of cardiac function in IR rats. Further, acute rHDL infusion in carotid vessels reduced remnant lipoprotein associated-cholesterol deposition (30–86%; **p < 0.01) ex vivo in IR and male Wistar rats and reduced (41%; *p < 0.05) the frequency of early-stage myocardial lesions in IR rats. CONCLUSION Short-term infusion of rHDL may beneficially reduce chronic vascular sequelae of MetS, including temporary improvement in LV-dysfunction, acute reduction of acute arterial cholesterol deposition and the development of early-stage myocardial lesions in the JCR:LA-cp rat.